Modern Legal Frameworks And Methods Of Promoting Team Sports In Uzbekistan (Zien Journal of Social Sciences and Humanities, 2025)
This article explores the existing regulatory framework for promoting team sports in New Uzbekistan and strategies for engaging young people in these activities. It provides an overview of relevant legislative acts and highlights the significance of popularizing team sports in fostering a strong awareness of healthy living among youth. The suggested approaches for effectively motivating students and schoolchildren to participate in team sports focus on enhancing sports infrastructure and encouraging greater youth involvement in sports.